GROWTH, YIELD AND EARLINESS RESPONSE OF COTTON TO ROW SPACING AND NITROGEN MANAGEMENT - M. K. Munir1; M. Tahir; M. F. Saleem; M.Yaseen (Journal of Animal and Plant Sciences, 2015)
Agronomic practices may significantly influence earliness and yield in cotton (Gossypium hirsutum L.). The present study was designed to evaluate the effect of row spacing and nitrogen on earliness and yield in cotton on a loam soil at Post Graduate Agricultural Research Station, University of Agriculture Faisalabad, during the year 2007 and 2008. Three row spacings of 60, 75 and 90 cm were established as the whole plots and four nitrogen fertilizer rates of 0, 60,120 and 180 kg N ha-1 were applied as the split plots. Both the factors significantly influenced plant height, main stem nodes, number of bolls per plant, boll weight and seed cotton yield per hectare. There were no significant differences between row spacings for earliness index but crop maturity hastened with lower N rates. The maximum seed cotton yield (2106 and 1936 kg ha-1 in 2007 and 2008, respectively) was recorded from 75 cm row spacing probably due to more number of bolls m-2. Similarly, highest seed cotton yield (2197 and 2032 kg ha-1 in 2007 and 2008, respectively) was produced by applying 180 kg N ha-1 which was also statistically similar to 120 kg N ha-1 during both experimental years. For optimum seed cotton yield, cotton should be sown on 75 cm spaced rows with 120 kg ha-1 of nitrogen.
Keywords: Gossypium hirsutum; nitrogen; row spacing; earliness and seed cotton yield